Game On: Tempting Twenty-Eight - Evanovich, Janet (New York : Atria Books, 2021)
"When Stephanie Plum is woken up in the middle of the night by the sound of footsteps in her apartment, she wishes she didn't keep her gun in the cookie jar in her kitchen. And when she finds out the intruder is fellow apprehension agent Diesel, six feet of hard muscle and bad attitude who she hasn't seen in more than two years, she still thinks the gun might come in handy. Turns out Diesel and Stephanie are on the trail of the same fugitive: Oswald Wednesday, an international computer hacker as brilliant as he is ruthless. Unsure if Diesel is her partner or her competition in this case, she'll need to watch her back every step of the way as she sets the stage to draw Wednesday out from behind his computer and into the real world"--
Keywords: Plum, Stephanie -- (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; Bounty hunters -- Fiction; Bail bond agents -- Fiction -- New Jersey; Hackers -- Fiction; Trenton (N.J.) -- Fiction; Detective and mystery fiction; Humorous fiction